Performance Analysis Of “Toga” Foundation With Cap On Thick Soft Soil Based On Laboratory Models And Finite Element Analysis - Melissa Kurnia; Paulus Pramono Rahardjo (U Karst, 2020)
Various alternative foundations are offered depending on soil conditions from the results of soil investigations. In difficult soil types such as thick, soft soil layers, pile foundation is generally used to avoid the excess settlements, but deep foundations for small buildings are not the right solution when viewed from a cost perspective. One of the more economical foundations is to use the” toga” foundation, with a plate on top and a caisson underneath where the caisson can be inserted into the soil with an open end. Through this study, the carrying capacity of the” toga” foundation will be analyzed. Then the foundation will be made on a laboratory scale and tested with axial load. The load and deformation relationship were analyzed using PLAXIS 3D analysis. It can be concluded the performance of the ”toga” foundation on thick, soft soil can be used for two-floored buildings